What makes a champion for landscape-based storm water management in Addis Ababa?. (April 2019) - Habtemariam, Liku Workalemahu; Herslund, Lise Byskov; Mguni, Patience
Highlights: Among the critical issues of sustainability in urban water is the transition to more sustainable configuration. Champions of landscape-based storm water management are needed to transition cities of the Global South. Workshops, focal group discussion, and interviews conducted to identify challenges and opportunities of emerging champions. Four types of emerging champions – project, local-level, executive, and intermediaries identified. Universities can play an important role as intermediaries but need to be supported with resources and other type of champions. Abstract: The Literature on cities in the Global North places champions at the centre of transitions in the water sector. But what makes a champion in a city of the Global South like Addis Ababa where the capacity and level of coordination is low? In this article, a case study based on different action research activities including workshops, training, plan making as well as interviews, was conducted to identify the conditions that makes a champion and to highlight the challenges and opportunities for fostering champions of landscape-based storm water management (LSM). The study shows that potential executive champions are difficult to engage which is a problem in a hierarchical and centralized governance system, leaving little room for potential project level champions to manoeuvre. High turnover of staff both among executives and experts presents a barrier to the fostering of champions. Local-level champions are needed; however there are structural constraints that impede their emergence. The university as an intermediary can play a big role in fostering champions of LSM, but it can also burnout and thus other types of champions are needed.